Global numerical simulation of heat and mass transfer for SiC bulk crystal growth by PVT - Selder, Markus; Kadinski, Lev; Makarov, Y.; Durst, Franz; Wellmann, Peter; Straubinger, Thomas; Hofmann, Heinz-Dieter; Karpov, S.; Ramm, M. (Journal of Crystal Growth, 2000)
A modeling approach for the numerical simulation of heat and mass transfer during SiC sublimation growth in inductively heated physical vapor transport (PVT) reactors is introduced. The physical model is based on the two-dimensional solution of the coupled differential equations describing mass conservation, momentum conservation, conjugate heat transfer including surface to surface radiation, multicomponent chemical species mass transfer and advective flow. The model also includes the Joule volume heat sources induced by the electromagnetic field. The evolution of the temperature profiles inside the crucible and of the crystallization front is studied. The radial temperature gradient at the crystal/gas interface causes strong radial non-uniformity of the growth rate and, in turn, influences the shape of the growing crystal. Results of calculations are compared to experimental observations to analyse the validity of the modeling approach. Both the computed growth rates, their temporal evolution and the shape of the growing crystal agree with experimental dat
UnivIS-Import:2015-10-26:Pub.2000.tech.ITC.stmmec.global
Keywords: SiC bulk growth; Physical vapor transport; Numerical modeling; Global heat and mass transfer